ANALISIS KONSEP DASAR ASSESMEN BIMBINGAN DAN KONSELING DALAM KONTEKS PENDIDIKAN - Wenda Asmita; Wahidah Fitriani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
The basic thing needed by counselors in implementing a BK program is an assessment. The reality on the ground is that there are some counselors who still use that assessment and that's all. So there needs to be a re-understanding by the BK teacher regarding the basic concepts of the assessment itself. The method used is a literature study, which aims to help counseling counselors/teachers understand the basic concepts of BK assessment in the context of education. The novelty of this article is supplemented by analysis that will assist in understanding the context in which it is discussed. In conclusion, assessment is a basic thing that must be mastered by counselors in order to more easily classify programs according to client problems.